Data Acquisition of a Tensile Test Stand for Cryogenic Environment - Heiduk, M.; Bagrets, N.; Weiss, K. P. (IEEE transactions on applied superconductivity, 2012)
Superconducting magnets and components are exposed to mechanical forces during cool down or current operation. The mechanical strength of used materials has to fulfill the specified requirements. A tensile test in cryogenic environment is one option in material testing to assess usability of materials. The PHOENIX facility at Karlsruhe Institute of Technology-Institute for Technical Physics is designated to analyse specimen on tensile load under cryogenic conditions. PHOENIX was adapted for economic operation. A total number of ten samples can be tested one after the other during one cool down cycle. PHOENIX is subject to a quality management system and it is planned to be accredited according to ISO 17025 standard in the near future. Focus of work will be the qualification of steel samples for quality assurance of cryogenic magnet components of the poloidal field and toroidal field coils in the framework of the ITER project. Recent instrumentation and software provide a standard degree of automation for the measurement tasks to be performed during a tensile test. The paper describes instrumentation equipment and implemented software features of the measurement and control system.